Analysis of the Effectiveness of the DPRD's Supervision Function on Batam City Regional Government Performance - Putra Yustisi Respaty; Erniyanti Erniyanti; Darwis Anatami; Soerya Respationo (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM), Sekolah Tinggi Ilmu Ekonomi Krakatau, 2025)
Purpose: This study analyzes the effectiveness of the Batam City DPRD’s supervisory function and the factors affecting it, amid challenges like limited resources, political intervention, low public access to information, and suboptimal member competence. Methodology/approach: This study uses normative juridical and sociological empirical methods through literature review and fieldwork involving DPRD members, local officials, and the public, with descriptive analysis of supervision aspects like DPRD involvement, transparency, government response, and public participation. Results/findings: The Batam City DPRD’s supervisory function is hindered by limited resources, political interference, low public participation, and weak member capacity, though active involvement and government response help improve its effectiveness. Conclusions: The study concludes that Batam City DPRD's oversight is essential but limited by internal and external factors. Improving member competence, public involvement, and minimizing political interference are key to strengthening its effectiveness. Limitations: This study is limited to the context of the Batam City DPRD and may not reflect conditions in other regions. The findings are also based on qualitative data, which may be subject to respondent bias and limited generalizability. Contribution:. This research identifies key factors in DPRD oversight and provides insights to improve legislative governance and guide future studies on regional legislative performance.